(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
Recently a series of films made by immigrants to Italy have emerged. These nevertheless remain marginal to the national industry, in part as Italy has no centralized policies that support the development of a “new Italian cinema” legally. This affects the production/distribution strategies and representational modes of migration cinema. This essay focuses on MigrArti, a call opened by MiBAC in 2015, which promotes creative initiatives in the fields of cinema, music, theatre and art, enabling migrants to introduce their traditions and their values in Italian society and culture. The objective is threefold: to question the concept of "Italian cinema" in relation to cultural shifts; to provide a picture of the funding of migrant cinema in Italy; to analyse the structure of the MigrArti call, in order to understand which subjects, production/distribution models and themes gain support, and why.